A novel petri nets algorithm using conditional probability for the evaluation of composite power system reliability - Thotakura, Bharath kumar; Borra, Hema Bhargavi; Alla, Chinmai (International Journal of Engineering and Technology, 2018)
Reliability of an electrical power system plays a vital role in providing continuous power supply to consumers with greater quality. The power demand is increasing day by day due to the increased population, modern society and are seeking highly reliable power. The assessment of reliability is very difficult due to the presence of large number of components and complex power system network con-figurations. This paper address a novel useful step by step algorithm for the assessment of average power availability at load buses us-ing the concept of modified Petri nets with conditional probability. The proposed algorithm is very efficient and can applicable to any number of the bus system. The proposed algorithm is tested with Roy Billiton practical example, IEEE 6 bus, IEEE 14 bus and IEEE RTS-96 bus system. The obtained results are validated by Monte Carlo simulation method, Classical Node elimination method and mod-ified minimal cut set method.